Peran IAHN-TP Palangka Raya Dalam Melestarikan Identitas Kultural Penganut Hindu Kaharingan Di Kalimantan Tengah - Nali Eka (Jayapangus Press, 2022)
Previous research on Kaharingan has written more about various rituals and the integration of Kaharingan with Hinduism. While this paper aims to describe the role of Hindu Universities which have the responsibility to build and improve the quality of Hindu human resourches who have global competence. But still not uprooted from its cultural roots, one way is by participating in caring for and preserving the teachings of local wisdom. Where this lokal wisdom also has profitable potential. This descriptive-qualitative research uses a phenomenological approach to cultural adaptatioan and receptioan theory. The result of the studi showed that the Hindu Institute of Tampung Penyang Palangka Raya state as the Hindu religios College in Kalimantan applies a global minded education pattern to answer the demans of globalization and Hindu educatioan based on local wisdom Kaharingan as identity or cultural identity. The application of this local wisdom based education in the form of local wisdom courses such as Tawur, Tandak, Acara Agama Hindu Kaharingan, Panaturan, Bahasa Sangiang, Bahasa Daerah, Teologi Hindu Kaharingan and other Kaharingan local wisdom courses. Universities have roles and responsibility to mentain local wisdom as the identity of a community, so that Hindu human resource are competitive in facing the challenges of globalization, but are still not uprooted from their cultural roots.